PERBANDINGAN SUBSTANSIAL MENGENAI DEFINISI DAN RUANG LINGKUP MEREK ANTARA UNDANG-UNDANG MEREK 2001 DAN 2016 - Sujana Donandi. S (Problematika Hukum, 2018)
In this era of globalization and improving technology, the law of trademark is expected to adapt the society factual needs, especially in giving the boundary of definition and scope of trademark. Trademark regulation in Indonesia was previously govermed in Law Number 15 Year 2001 which has been revised by Law Number 20 Year 2016 concerning Trademark and Geographical Indication. This new law is expected to present updates on values which could reach the business practice nowadays compare to the old law. This research aims to do a substantial comparison regarding definition and scope of trademark between trademark law 2001 and 2016. This research is done using normative legal research method through comparison approach. The result shows that the definition of trademark has improved from law 2001 to 2016 by the existence of a more specific definition on trademark by adding provision regarding the shape of trademark both in two dimension and/or three dimension, voices, and hologram. Nevertheless, this definition does not clearly govern on trademark that particularly used in internet. Moreover, the trademark classification has no change that trademarks are still divided into trading trademark, service trademark, and collective trademark. Legal sytem of trademark protection is also remain the same, using the constitutive system. Regarding the trademark the can not be registered and the rejected application also has no significant change, except the additional arrangement on the trademark that can not be registered which is now including the trademark which contains element that can cause misleading to the society concerning on the origin, quality, type, size, classification, objective of the goods and or service applied, or for it is similar to names of protected plant variety for the same types of goods and or service, as well as contains information which is not appropriate to the quality, function, or benefits of the produced goods and or services.